If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9p + -5p + -9 + -2p = 10 Reorder the terms: -9 + 9p + -5p + -2p = 10 Combine like terms: 9p + -5p = 4p -9 + 4p + -2p = 10 Combine like terms: 4p + -2p = 2p -9 + 2p = 10 Solving -9 + 2p = 10 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + 2p = 10 + 9 Combine like terms: -9 + 9 = 0 0 + 2p = 10 + 9 2p = 10 + 9 Combine like terms: 10 + 9 = 19 2p = 19 Divide each side by '2'. p = 9.5 Simplifying p = 9.5
| 6a-16=2(a-6) | | 16=6ty | | 16=6tyv | | 3.045+3b=2.73b+2.4+0.7b | | 8n+22=3 | | -7/2=-6/5x-7/3 | | 5+6p=41 | | -12/k=-4 | | 1(2x-4)=2(4-6x) | | 13/20-1/6 | | 18+6m=5+(-4m) | | 3(x-3)=6x-6-3x | | 70-42y-y=0 | | -12=4-n | | 5e+15=4e+8 | | 3x+3y=102 | | 1x/9 | | 1/2(2x-4)=2(4-6x) | | y=7500+19x | | 7b+13=3b-17 | | 18-6m=5-4m | | 3a+5b-7b= | | n+n+1+n+2=27 | | 2(w-4)=8w+10 | | 6/7=x/10.5 | | 27x-3=51 | | 2a+8=3a-1 | | 51x-3=27 | | 5(x-2)=5x-11 | | 2(x+10)+3x=85 | | 51x-27=3 | | 32-5x=50-3x |